Analysis of New Normal Era of Jurisprudence Learning Management at Islamic High School: Analisa Manajemen Pembelajaran Fikih Era New Normal di Sekolah Menengah Atas Islam - Febiyanto, Fahmita Ramadhan; Fauji, Imam (Adabiyah: Jurnal Pendidikan Islam, 2023)
The analysis of Fiqh learning management in the new normal era at MAN 2 Mojokerto includes planning, implementation, monitoring and evaluation based on e-learning with online learning methods that are based on quotas and internet networks. The purpose of this study is to determine, analyze and provide alternative solutions related to the inhibiting and supporting factors for the management of Fiqh learning in the new normal era of MAN 2 Mojokerto. This research is included in descriptive qualitative with a phenomenological approach. Data collection techniques are interviews, observation, and documentation with primary and secondary data sources. Analysis and interpretation of data by reduction, presentation and conclusion. The results of the research on Fiqh learning management in the new normal era at MAN 2 Mojokerto include planning, implementation, supervision, and evaluation. The inhibiting and supporting factors are felt by educators, students and parents with solutions for free quota assistance from schools, debriefing for teachers and students, and tolerance for assignments as a substitute for learning.